2013
DOI: 10.1103/physreve.88.042820
|View full text |Cite
|
Sign up to set email alerts
|

Effects of local population structure in a reaction-diffusion model of a contact process on metapopulation networks

Abstract: We investigate the effects of local population structure in reaction-diffusion processes representing a contact process (CP) on metapopulations represented as complex networks. Considering a model in which the nodes of a large scale network represent local populations defined in terms of a homogeneous graph, we show by means of extensive numerical simulations that the critical properties of the reaction-diffusion system are independent of the local population structure, even when this one is given by a ordered… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 43 publications
(81 reference statements)
4
21
0
1
Order By: Relevance
“…These models generally assume homogeneous mixing within patches where the infection dynamics takes place (or mixing between population groups [47]) and either an effective coupling between patches or explicit migration/mobility processes. While non-Markovian rules have been introduced in migration processes in metapopulation models for the study of disease spread and epidemic threshold conditions [48][49][50][51], explicit contact structure between individuals in a patch have been rarely considered [52], assuming static topologies. Our approach thus differs from usual metapopulation models in that it provides explicit temporally evolving contact structures within each group, allowing for different possible dynamics of mobility and contacts.…”
Section: Agent-based Model Of Interaction Dynamicsmentioning
confidence: 99%
“…These models generally assume homogeneous mixing within patches where the infection dynamics takes place (or mixing between population groups [47]) and either an effective coupling between patches or explicit migration/mobility processes. While non-Markovian rules have been introduced in migration processes in metapopulation models for the study of disease spread and epidemic threshold conditions [48][49][50][51], explicit contact structure between individuals in a patch have been rarely considered [52], assuming static topologies. Our approach thus differs from usual metapopulation models in that it provides explicit temporally evolving contact structures within each group, allowing for different possible dynamics of mobility and contacts.…”
Section: Agent-based Model Of Interaction Dynamicsmentioning
confidence: 99%
“…Using heterogeneous mean-field (HMF) theory and assuming that subpopulations with the same degree are statistical equivalent, Colizza and Vespignani proposed two models to describe transmission of diseases on heterogeneous metapopulation networks under two different mobility patterns, which sheds light on calculation of global invasion threshold [7] . Next, different network structures, including bipartite metapopulation network [8] , time-varying metapopulation network [9] , local subpopulation structure [10] , interconnected metapopulation network [11] , have been found to play an essential role in the global spread of infectious diseases. Furthermore, studies have shown that adaptive behavior of individuals contributes to the global spread of epidemics, contrary to willingness [12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Relevance of the interplay between diffusion and epidemic spreading in real systems is self-evident since hosts of infectious agents, such as people and mobile devices, are constantly moving and being the carriers that promote the quick transition from a localized outbreak to a large scale epidemics 4,5,15 . Diffusion has been investigated on networks for bosonic epidemic processes where the vertices can be simultaneously occupied by several individuals 18 and, in particular, within the context of heterogeneous metapopulations [19][20][21][22][23] where each vertex consists itself of a subpopulation and the edges represent possibility of interchange of individuals moving from one subpopulation to another according to a mobility rule. When infected and healthy individuals move with the same rate on a metapopulation, the concentration of both types is proportional to the vertex degree 20 .…”
Section: Introductionmentioning
confidence: 99%